2019
DOI: 10.3390/ijms20092154
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory, Serological and Vascular Determinants of Cardiovascular Disease in Systemic Lupus Erythematosus Patients

Abstract: Background and aim: Systemic lupus erythematosus (SLE) is associated with increased risk of cardiovascular disease (CVD). Among many mechanisms, accelerated atherosclerosis, endothelial dysfunction, and hypercoagulability play a main role. Here, we investigate whether inflammatory, serological and clinical markers of SLE determine and correlate with arterial stiffness in SLE patients. Materials and methods: Routine blood samples, inflammatory mediators, specific antibodies, and 24 h proteinuria were measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
(55 reference statements)
0
22
0
1
Order By: Relevance
“…The special issue, entitled “Mechanisms of inflammation in degenerative cardiovascular conditions”, presents 14 contributions that highlight the recent advances in the mechanisms of inflammation in cardiovascular diseases. In particular, these studies sustain the proof of concept that inflammation represents a significant cardiovascular risk factor [2,3,4,5] and is also mandatory to the development of both cardiac [2,3,5,6,7,8,9,10,11] and vascular events [4,12,13,14,15], and can be targeted using specific and non-specific therapeutics [8].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…The special issue, entitled “Mechanisms of inflammation in degenerative cardiovascular conditions”, presents 14 contributions that highlight the recent advances in the mechanisms of inflammation in cardiovascular diseases. In particular, these studies sustain the proof of concept that inflammation represents a significant cardiovascular risk factor [2,3,4,5] and is also mandatory to the development of both cardiac [2,3,5,6,7,8,9,10,11] and vascular events [4,12,13,14,15], and can be targeted using specific and non-specific therapeutics [8].…”
Section: Introductionmentioning
confidence: 55%
“…Moreover, inflammatory markers (i.e., PCR levels) predict a worse survival during acute coronary syndromes [2]. Accordingly, cardiovascular risk increases in patients with chronic inflammatory diseases such as rheumatoid arthritis [2], systemic lupus erythematosus [4], periodontitis [3], and atopic dermatitis [5]. Mercurio and colleagues showed that in patients with lupus erythematosus the increased arterial stiffness significantly correlates with several markers of inflammation [4].…”
Section: Inflammation As a Cardiovascular Risk Factormentioning
confidence: 99%
“…Accelerated atherosclerosis in SLE has been related to traditional risk factors and some SLE related factors such as disease duration, steroid therapy, activity, organ damage [5] [8] [9] [10]. In previous studies, the major determinants of low ABI were age and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional cardiovascular factors (including Diabetes mellitus, hypertension, tobacco, atherogenic dyslipidemia), SLE therapies such as corticosteroid and disease-related factors (subclinical inflammation, oxidative stress, antiphospholipid antibodies) appear to contribute to the increasing of incidence of cardiovascular events in SLE [5] [8] [9] [10].…”
Section: Introductionmentioning
confidence: 99%
“…The balance between the stability and instability of the atherosclerotic plaque induced by cellular apoptosis, secretion of matrix metalloproteases, and severe inflammation determines the fate of the plaque and the risk of sudden events. Various chronic infectious (e.g., periodontitis) and inflammatory diseases (e.g., rheumatoid arthritis, systemic lupus erythematosus, and psoriasis) are significant risk factors for cardiovascular events [11,12].…”
Section: Introductionmentioning
confidence: 99%